HEALTH EDUCATION TO IMPROVE MOTHER'S ABILITY IN INFANT PERIANAL CARE - Ayuda Nia Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2021)
Background: The skin is a very important part because it functions as a protector. In newborns, which do not have a good skin structure, it can cause various health problems, such as: infection, irritation, and allergies. One of the efforts that can be done to prevent skin disorders, especially in the groin area is to do proper perianal care. Purpose: The purpose of this study was to describe the provision of education to improve the knowledge and skills of mothers in caring for the perianal area of ??infants. Method: The research design used was descriptive with case studies, involving 2 mothers and 2 babies who were selected based on inclusion criteria. The instruments used were questionnaires and observation sheets of maternal skills in performing perianal care. Data presented in a narrative about perianal care of infants by mothers to overcome nursing diagnoses of the risk of damage to the integrity of the baby's skin. The research was conducted at Fatmawati Hospital, Perinatology room for 5 days. The main procedure in this study is providing education and training the skills of mothers in proper perianal care. Result: The results showed that there was an increase in the knowledge and skills of mothers in caring for perianal babies, this was indicated by the average score of knowledge for the two mothers before being given education was 4 and after being given education was 9. The skills of both mothers were in the less skilled category in caring for the perianal area. to be able to do self-care and correct. Conclusion: Providing education can increase the knowledge and skills of mothers in caring for the baby's perianal area. Providing education, mentoring skills to mothers can make mothers more confident when caring for babies at home. Researchers recommend that room nurses make standard operating procedures for care of the perianal area and carry out optimal education. Keywords: Mother's knowledge and skills, Neonates, Perianal Care